2021
DOI: 10.9734/aprj/2021/v7i430162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxicological Profile of Yagari

Abstract: Background and Objective: Data from researches have shown a rise in disease, ill health and death linked with the utilization of herbal products, thereby raising global awareness in the last few years. On that account, the safety and toxicity evaluations of herbal products and preparations was essential. This study evaluated the toxicological profile of Yagari – a herbal mixture. Materials and Methods: Acute oral toxicity (LD50) was carried out in Swiss mice according to Lorke’s method while sub-chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…The liver photomicrographs showed that treatment of animals with the polyherbal mixtures did not induce any visible lesions or derangements in the examined organ. [77][78][79][80][81][82][83][84] However, in the sub-acute toxicity study of Hab-e-Kabad Noshadri tablets used for the treatment of hepatitis, enlargement of liver at doses of 100 and and 200 mg/kg/day, morphological changes with some damage in liver and kidney tissues of male and female animals was observed. Hence, prolonged use at higher dose i.e.…”
Section: Toxicological Activity Of Polyherbal Formulationsmentioning
confidence: 99%
“…The liver photomicrographs showed that treatment of animals with the polyherbal mixtures did not induce any visible lesions or derangements in the examined organ. [77][78][79][80][81][82][83][84] However, in the sub-acute toxicity study of Hab-e-Kabad Noshadri tablets used for the treatment of hepatitis, enlargement of liver at doses of 100 and and 200 mg/kg/day, morphological changes with some damage in liver and kidney tissues of male and female animals was observed. Hence, prolonged use at higher dose i.e.…”
Section: Toxicological Activity Of Polyherbal Formulationsmentioning
confidence: 99%